The extradition process and its importance regarding the fight against criminality - Ugaz Zegarra, Ángel Fernando (2022)
In this article, we analyze the extradition process from its origin in international criminal law, as well as its treatment in Peru and the procedure that must be followed to achieve extradition. Likewise, we develop the ruling of the Wong Ho Wing versus Peru case, in which the right to a trial within a reasonable time and personal liberty were violated in an extradition process, due to the delay in its conclusion and the excessive time that he was deprived of his liberty by the Peruvian authorities.